Altered glucose metabolism and proteolysis in pancreatic cancer cell conditioned myoblasts: searching for a gene expression pattern with a microarray analysis of 5000 skeletal muscle genes. Issue 8 (9th July 2004) - Basso, D; Millino, C; Greco, E; Romualdi, C; Fogar, P; Valerio, A; Bellin, M; Zambon, C-F; Navaglia, F; Dussini, N; Avogaro, A; Pedrazzoli, S; et al.
Abstract : Background and aims: We verified whether conditioned media (CM) from pancreatic cancer cell lines (MIAPaCa2, CAPAN-1, PANC-1, BxPC3) alter glucose metabolism and gene expression profiles (microarray experiment with a platform of 5000 skeletal muscle cDNA) in mice myoblasts. Methods: Myoblasts were incubated with control or pancreatic cancer CM for 24 and 48 hours. Results: Lactate significantly increased in CM compared with non-conditioned myoblasts. No variations in expression levels of the main genes involved in glycolysis were found in CM myoblasts. Propionyl coenzyme A carboxylase and isocitrate dehydrogenase 3 beta genes, which encode enzymes of the tricarboxylic acid cycle, were overexpressed, while IGFIIR and VAMP5 genes were underexpressed in CM myoblasts. PAFAH1B1 and BCL-2 genes (intracellular signal transduction) and the serine protease cathepsin G (proteolysis), were overexpressed in CM myoblasts. Tyrosine accumulation in CM myoblasts suggested that proteolysis overcomes protein synthesis. Sorcin, actin alpha, troponin T1, and filamin A were underexpressed in CM myoblasts. Conclusions: Our findings demonstrate that pancreatic cancer cell conditioned media enhanced lactate production and induced proteolysis, possibly by altering expression levels of a large number of genes, not only those involved in protein biosynthesis and degradation or glucose metabolism, but also those involved in the tricarboxylic acid cycle and in vesicle traffic.